Eagles fly - Flannery, Sean (New York : Forge, 1998)
"It begins in Buenos Aires where two men lay dead, each the victim of a gruesome attack. It continues in the United States, where Dr. Richard Kelsey is brought a patient who may hold the key to solving the crimes. Dr. Kelsey's life is turned upside down as he is sucked into a bizarre conspiracy, one that may threaten the political stability of the free world."--Cover.
National College of Business and Arts
Keywords: Murder -- Fiction; Thrillers (Fiction)